Counting an Invisible Class of Citizens: The LGBT Population and the U.S. Census. (2nd January 2020) - Naylor, Lorenda A.
Abstract : Due to past discrimination, recent U.S. Supreme Court cases and federal legislation have expanded the legal rights of LGBT citizens in marriage equality ( Obergefell v. Hodges, 576_US 2015; U.S. v. Windsor, 570 U.S. 2013), sexual privacy ( Lawrence v. Texas, 539 U.S. 558, 2003), military service (repeal of Don't Ask Don't Tell Act of 1993), and hate crime protection (The Matthew Shephard and James Byrd, Jr. Hate Crimes Prevention Act of 2009). These policy milestones laid the foundation for securing additional rights. However, in 2017 the U.S. Census Bureau announced it would not collect LGBT demographic data, specifically sexual orientation and gender identity, in the upcoming 2020 Census (Thompson, 2017) representing a major setback to LGBT citizens who viewed it as creating an invisible class of citizens. Gleaning from the framework of social equity (Frederickson, 2010; Johnson, & Svara, 2011) and intersectionality (Crenshaw, 1989a), this manuscript evaluates the U.S. Census Bureau's decision to omit LGBT demographic data. Using the agency's data as the standard, empirical evidence supports the inclusion of LGBT demographic variables in the census. Policy recommendations are provided to ensure LGBT citizens are included in the census and assimilated into mainstream America.